Breastfeeding Ambivalence Among Low-Income African American and Puerto Rican Women in North and Central Brooklyn. - Kaufman L; Deenadayalan S; Karpati A (Maternal & Child Health Journal, 2010)
This study explores low-income African American and Puerto Rican women’s conceptions and practices around breastfeeding. It examines the impact of such diverse factors as social constructions of the body, local mores around infant care, the practicalities of food availability, in the context of interactions with family members and friends, institutions, and others in women’s neighborhoods. The study employed ethnographic methods, including interviews and participant observation, with 28 families in two low-income Brooklyn neighborhoods. While women in this study felt that breastfeeding was the best way to feed their infants, their commitment turned to ambivalence in the face of their perceptions about the dangers of breast milk, the virtues of formula, and the practical and sociocultural challenges of breastfeeding. Women’s ambivalence resulted in a widespread complementary feeding pattern that included breast milk and formula, and resulted in short breastfeeding durations. Findings suggest the critical role of breastfeeding “ambivalence” in driving thought and action in women’s lives. Ambivalence erodes the permanence of breastfeeding intention, and makes feeding practices provisional. Ambivalence challenges breastfeeding promotion strategies, resulting in weakened public health messages and a difficult-to-realize public health goal.